Sapient : defining success was both the challenge and the opportunity - Nagy, Andrea; Elias, Jaan; Podolny, Joel M. (Joel Marc) ([London] : SAGE, 2016)
Although Sapient was categorized as a marketing, business, and technology consulting company, employees insisted that they never sold consulting or provided mere deliverables. Instead, Sapient promised "client success" and to this end had articulated a model with three principles that the company perceived as central to its value proposition. For Sapient, 'client success' was not a rhetorical gesture or a marketing slogan but a philosophy that permeated the way the company approached every client. Maintaining a client focus was one of the core values that the co-founders of Sapient, Jerry Greenberg and Stuart Moore, articulated soon after they started their technology consulting company in 1990.
Originally Published in: Nagy, A., Elias, J., & Podolny, J. (2007). Sapient: Defining Success Was Both the Challenge and the Opportunity. 06-017. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Success in business -- Case studies